Utilização da farinha de grão-de-bico na elaboração de biscoitos tipo cookies - (:unkn) unknown (Universidade Federal do Pampa, 2013)
The garbanzo beans are an excellent source of proteins, carbohydrates, minerals, vitamins and fiber has a low content of antinutritional substances and high availability of iron. A mixture of leguminous flour in bakery products has shown to improve protein quality and nutritional value of this type of product. This study aimed to evaluate the effect of partial substitution of wheat flour (FT) for chickpea flour chickpeas (FGB) on the technological characteristics of type biscuits cookies. Five formulations were prepared cookie with partial substitution of FT, for FGB in the ratios of 100:0 (F1), 90:10 (F2), 80:20 (F3), 70:30 (F4) and 60:40 (F5) respectively, and the remaining ingredients remained constant in different formulations. To characterize the cookies were evaluated as thickness, diameter and specific volume, texture, and color of the same instrument. The results indicated that the addition range studied FGB not significant (p> 0.05) in thickness and diameter of the cookies, so the addition of more than 30% FGB promoted an increase in hardness. The increase in color by the addition of FGB was a decrease in luminosity (L) and an increase in the values of the parameter a *, however not influence the b * parameter. All formulations showed acceptable technological characteristics. The highest scores were assigned to the flavor, texture and aroma. Regarding the intention to purchase the formulation F5 was better evaluated, so it was possible to add up to 40% of chickpea flour chickpeas in formulations bicoitos without changing technological characteristics, with good acceptability and presents potential higher nutritional value.
Keywords: Cicer arietinum L; Proteínas; Fibras; Panificação; Protein; Fiber; Baking; CNPQ::CIENCIAS AGRARIAS